2012
DOI: 10.1051/0004-6361/201116512
|View full text |Cite
|
Sign up to set email alerts
|

Stellar populations in the Milky Way bulge region: towards solving the Galactic bulge and bar shapes using 2MASS data

Abstract: Exploring the bulge region of our Galaxy is an interesting but challenging quest because of its complex structure and the highly variable extinction. We re-analyse photometric near-infrared data in order to investigate why it is so hard to reach a consensus on the shape and density law of the bulge, as witnessed in the literature. The apparent orientation of the bulge seems to vary with the range of longitude, latitude, and the population considered. To solve the problem we have used the Besançon galaxy model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
315
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 252 publications
(325 citation statements)
references
References 46 publications
8
315
0
2
Order By: Relevance
“…In a recent review, Babusiaux (2012) concluded that the other characteristics point toward a mix of stellar populations although the main shape of the GB seems to be driven by secular evolution. This multi-component structure is also seen in the shape of the GB (Robin et al 2012), which may be a combination of a classical and a pseudo (box-shape) bar.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent review, Babusiaux (2012) concluded that the other characteristics point toward a mix of stellar populations although the main shape of the GB seems to be driven by secular evolution. This multi-component structure is also seen in the shape of the GB (Robin et al 2012), which may be a combination of a classical and a pseudo (box-shape) bar.…”
Section: Introductionmentioning
confidence: 98%
“…The PNe trace populations which have ages ranging from <1 to 10 Gyr. In contrast, red clump data analysis, as used by Robin et al (2012), cannot discriminate any ages over 5 Gyr. However, deriving ages for the central stars of individual PNe has been a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The model is by no means the only choice -alternatives being TRILEGAL (Girardi et al 2005), the models of Ng et al (1997) and Vallenari et al (1999), as well as the BGM-derived approach Galaxia (Sharma et al 2011). Here we use the scheme of the BGM described in Robin et al (2003), updated by Reylé et al (2009) for the warp and flare parameters, by Robin et al (2012) for the bulge and bar region, by Robin et al (2014;submitted) for the thick disc and halo shapes. The extinction model used is based on Marshall et al (2006); for the regions not included in this study the BGM uses a thin disc of diffuse extinction (Robin et al 2003).…”
Section: The New Besançon Modelmentioning
confidence: 99%
“…Recently, Robin et al (2012) presented a model where two populations co-exist in the bulge region: a bar or pseudo-bulge of high metallicity and small scale height, and a "thick bulge" or classical bulge with a higher scale height, lower metallicity, and higher velocity dispersion. This "Besançon model of the Galaxy" (BGM) explains well the apparent gradient in metallicity that is observed along the minor axis, by a variable proportion of the two populations of different scale height.…”
Section: Introductionmentioning
confidence: 99%